(untitled) (Scientific journal of the Fergana State University, 2024)
In accordance with the requirements of today’s dynamically developing era, the changing modern school education has faced many urgent tasks due to the need for a new approach to the content and structure of education. Now the modern student needs not to use traditional methods of teaching and upbringing, but to form and teach them the skills of independent learning and striving to improve the acquired knowledge. Therefore, the teacher himself must have professional and technical skills, be able to use new modern educational technologies that meet the requirements of modernity. The article examines the content of the concept of professional competence and the technology of its gradual development based on multimedia tools.